Modeling and Characteristics of an Axial-Gap Self-Bearing Motor - Nguyen, Huy Phuong (Old Journal, 2017)
Axial-gap self bearing motor (AGBM) is a functional combination of axial magnetic bearing and axial flux motor. It means the AGBM can generate rotation and translation with only three-phase windings. The paper will introduce about the characteristics of an AGBM. First the mathematical model of the AGBM is developed in rotor field-oriented coordinate. Then the axial force and the motoring torque are analyzed theoretically to confirm its abilities. In order to evaluate the rightness of the proposed theory, a single stator AGBM has been made and tested. The experimental results confirm that the levitation force is propotional to direct axis current (isd) and the rotary torque is propotional to quadrature axis current (isq).